(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Tourism has emerged as an important driver of economic activity in Asia, yet its growth implications remain closely intertwined with energy use and environmental sustainability. This study examines the long-run and short-run relationships among tourism receipts, economic growth, energy consumption and carbon emissions across 19 Asian economies over the period 2000-2023. Using panel data framework, the analysis employs Fully Modified Ordinary Least Squares (FMOLS), Dynamic Ordinary Least Squares (DOLS) and Granger Causality techniques to capture both equilibrium dynamics and short-term interactions. The results provide robust evidence in support of Tourism-Led Growth Hypothesis indicating that tourism development and energy consumption exert significant positive effects on income growth in the long run. In contrast, short-run causal relationships between tourism and growth are weak, suggesting that tourism’s macroeconomic benefits materialize gradually. Structural break analysis further reveals that the COVID-19 pandemic did not fundamentally alter the long-run tourism-growth relationship, highlighting the sector’s resilience despite severe sort-term disruptions. The findings emphasize the importance of sustainable tourism and energy policies in promoting long-term, inclusive economic growth.